Principles of Nanomagnetism - Guimarães, Alberto P. (Springer International Publishing : Imprint: Springer, 2017)
The second edition of this book on nanomagnetism presents the basics and latest studies of low-dimensional magnetic nano-objects. It highlights the intriguing properties of nanomagnetic objects, such as thin films, nanoparticles, nanowires, nanotubes, nanodisks and nanorings as well as novel phenomena like spin currents. It also describes how nanomagnetism was an important factor in the rapid evolution of high-density magnetic recording and is developing into a decisive element of spintronics. Further, it presents a number of biomedical applications. With exercises and solutions, it serves as a graduate textbook.
Keywords: Physics.; Magnetism.; Magnetic materials.; Nanotechnology.; elektronické knihy; electronic books